Effects of Exercise-Based Interventions on Neonatal Outcomes: A Meta-Analysis of Randomized Controlled Trials - Garcia-Hermoso, A (SAGE Publications Inc., 2016)
Objective: The aim of this study was to conduct a systematic review and meta-analysis of randomized controlled clinical trials (RCTs) assessing the influence of physical exercise interventions during pregnancy on some neonatal outcomes. Data Source: Key words were used to conduct a computerized search in six databases: Cochrane Library Plus, Science Direct, EMBASE, PubMed, Web of Science, and ClinicalTrials.gov. Study Inclusion and Exclusion Criteria: RCTs that included an exercise program for healthy pregnant women who were sedentary or had low levels of physical activity were selected. Data Extraction: Two independent reviewers extracted data and assessed the quality of the studies included. Of 4296 articles retrieved, 14 RCTs (3044 pregnant women) met the inclusion criteria. Data Synthesis: Pooled effect sizes (ESs) were calculated using a fixed model. Results: Overall, physical exercise programs during pregnancy produced a small reduction in neonatal birth weight (ES = -.10; p =.04). The Apgar score at 1 minute was also weakly increased with combined exercise (aerobic, strength, and flexibility) (ES =.09; p =.048) and no differences between groups were observed in gestational age at delivery and Apgar score at 5 minutes. Conclusion: Structured physical exercise programs during pregnancy appear to be safe for the neonate, mainly favoring a lower birth weight within normal range. However, more studies are needed to establish recommendations. © 2016 SAGE Publications.